Interoperable Electronic Safety Equipment Performance Requirements for Compatible and Interoperable Electronic Equipment for Emergency First Responders - Grant, Casey C.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2012)
Firefighters and other emergency first responders use a huge variety of highly specialized and critical technologies for personal protection. These technologies, ranging from GPS to environmental sensing to communication devices, often run on different systems with separate power supplies and operating platforms. How these technological components function in a single synergistic system is of critical interest to firefighter end-users seeking efficient tools. Interoperable ESE states that a standardized platform for electronic safety equipment (ESE) is both logical and essential. This book develops an inventory of existing and emerging electronic equipment categorized by key areas of interest to the fire service, documents equipment performance requirements relevant to interoperability, including communications and power requirements, and develops an action plan toward the development of requirements to meet the needs of emergency responders. This book is intended for practitioners as a tool for understanding interoperability concepts and the requirements of the fire service landscape. It offers clear recommendations for the future to help ensure efficiency and safety with fire protection equipment. Researchers working in a related field will also find the book valuable.
Introduction and Background -- Literature Review -- PPE Electronic Inventory -- Performance Requirements for Interoperability -- PPE Electronic Equipment Workshops -- Recommendations -- Bibliography -- Appendix.
Keywords: Computer science; Computer system performance; System safety; Civil engineering; Computer engineering; Computer Science; System Performance and Evaluation; Quality Control, Reliability, Safety and Risk; Electrical Engineering; Civil Engineering